Gods and generals - Ehlers, Corky; Frizzell, John; Edelman, Randy; Daniels, Jeff 1955-; Lang, Stephen 1952-; Duvall, Robert; Shaara, Jeff 1952-
Col. Joshua Lawrence Chamberlain leaves behind a quiet life and a career as a college professor to fight for the Union. Native Virginian Gen. Robert E. Lee is forced to choose between his loyalty to the United States and his love of the Southern states where he was born and raised, and leads the Confederate army. Gen. Thomas "Stonewall" Jackson -- a man of great religious faith -- believes in a higher authority leading him and his men to certain, pre-ordained fates, also serves in the defense of the Confederacy. The film follows Chamberlain, Jackson, and Lee from the declaration of war through the battles at Manassas, Antietam, Fredericksburg, and Chancellorsville